2013
DOI: 10.5830/cvja-2013-074
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the omega-3 fatty acid content of South African fish oil supplements : a follow-up study : cardiovascular topics

Abstract: IntroductionGlobally the omega-3 (n-3) fatty acid supplement industry is expanding rapidly while consumers are becoming more aware of the health benefits of n-3 fatty acids. Our group conducted a survey in 2009 on 45 commercially available fish oil supplements on the South African market. The aim of the study was to determine the fatty acid composition and content of supplements for comparison with the claimed contents on the product label. The survey was repeated in 2012 on 63 supplements.MethodsSixty-three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
2
26
0
3
Order By: Relevance
“…In addition, 25% exceeded the recommended level of secondary oxidation products (aldehydes and ketones) (4). Similar results have been demonstrated in studies from North America (36,50) and Africa (48). This implies that most women taking fish oil during pregnancy are routinely exposed to oxidation products.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…In addition, 25% exceeded the recommended level of secondary oxidation products (aldehydes and ketones) (4). Similar results have been demonstrated in studies from North America (36,50) and Africa (48). This implies that most women taking fish oil during pregnancy are routinely exposed to oxidation products.…”
supporting
confidence: 77%
“…It represents an important proof of concept that supplementation with oxidized fish oil in pregnancy may be harmful. This is relevant as fish oil supplements are often oxidized at the time of purchase (4,36,48,50) and are commonly taken during pregnancy. Therefore, there is a pressing need for studies examining dose-response relationships between oxidized fish oil consumption and pregnancy outcomes.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Recent studies have reported elevated peroxide levels in commercialised fish oil capsules, which have led to some concern that regular consumption of oxidised marine oils may negatively affect human health ( 16 21 ) . In a previous study, we did not observe any changes in fasting plasma LC n -3 FA levels, lipids or several other oxidative stress markers after 7 weeks of consumption of oxidised compared with non-oxidised fish oil ( 22 ) .…”
mentioning
confidence: 99%
“…The CD content, peroxide value and fatty acid analysis was determined according to the methods described in previous publications. 11 …”
Section: Methodsmentioning
confidence: 99%